Royal Patronage of Sanskrit & Mahmood Shah I - Dr. Arshad Mehmood Hashmi (دریافت)
It is a common notion that during the reign of Muslim kings or Sultans, Sanskrit was not given much attention, and that was one of the reasons it declined. Many research papers have appeared from time to time in support of and against this idea. Similarly, there are many contradictory statements in the books of History regarding Sultan Mahmood Shah I of Gujarat. Scholarships in recent years have pointed out some data that disprove many of the things that have been said about Mahmud Shah I. One of the aspects that have been highlighted is that he was not only a lover of Sanskrit language and literature, but also a mentor of Sanskrit, and in his court, a Sanskrit poet had the status of Malek-ush Sho'ara.